Assessment of a metal–organic framework catalyst in air cathode microbial fuel cells over time with different buffers and solutions. (June 2017) - Rossi, Ruggero; Yang, Wulin; Setti, Leonardo; Logan, Bruce E.
Highlights: Metal organic framework (MOF) catalysts greatly increased power using acetate. MOF cathodes had a larger percent decrease in power after 4 weeks than AC. Power after 8 weeks with MOF cathodes was still 41% higher than plain AC. Power with wastewater after 8 weeks was 53% higher than reported for Pt/C. Power using wastewater was more affected by changes in composition than time. Abstract: Metal–organic framework (MOF) on activated carbon (AC) enhanced the performance of cathodes but longevity needs to be considered in the presence of metal chelators or ligands, such as phosphate, present in wastewaters. MOF catalysts on AC initially produced 2.78 ± 0.08 W m −2, but power decreased by 26% after eight weeks in microbial fuel cells using a 50 mM phosphate buffer (PBS) and acetate due to decreased cathode performance. However, power was still 41% larger than that of the control AC (no MOF). Power generation using domestic wastewater was initially 0.73 ± 0.01 W m −2, and decreased by 21% over time, with power 53% larger than previous reports, although changes in wastewater composition were a factor in performance. Adding phosphate salts to the wastewater did not affect the catalyst performance over time. While MOF catalysts are therefore initially adversely affected by chelators, performance remains enhanced compared to plain AC.